CURRENT SITUATION OF CHILDREN AND ADOLESCENTS WITH HIV IN BRAZIL (Fiep Bulletin - online, 2011)
This is a descriptive study integrative literature review. The survey was conducted in the databases LILACS, books and online information, taking as keywords, AIDS, HIV, child, adolescent and health policies. The research objective was to discuss the scientific literature by the current situation of children and adolescents with HIV / AIDS in Brazil, as well as public policies and programs for health, targeted to them. As a result it was found that AIDS impacts the quality of life of children and young people who may suffer successive losses of living with his parents and possibly their relatives. Studies in Brazil have shown that the number of school-age children and adolescents living with HIV in services is increasing as a result of increased survival time. Considering the current situation of AIDS in the country and the conditions of social vulnerability of children and teenagers face the epidemic, the Brazilian STD / AIDS as outlined targets to reduce the incidence of HIV / AIDS, expanding access to diagnosis, treatment and assistance, and strengthening of public and private institutions responsible for controlling AIDS. It is important to emphasize that the Brazilian experience accumulated in the field of HIV / AIDS has shown that the construction of articulated public policies for health promotion and AIDS prevention should take into account poverty, violence and social and regional inequalities, as well as complexity of issues such as sexuality and drug use.
Keywords: HIV; child; health policies